Analisis Persepsi, Perilaku Dan Preferensi Masyarakat Terhadap Minat Menjadi Nasabah Bank Syariah - Waluyo, Bambang; Ameliasari, Fitri; Sixpria, Nedsal (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2023)
Indonesia is a Muslim-majority country, but the market share of Islamic banks in Indonesia is still low. Researchers have conducted pre-research to see how the perception and behavior of the merchant community in Pasar Parung towards Islamic banks. The pre-research shows differences in traders' perceptions of Islamic banks. In addition, there are also diverse behaviors and preferences toward Islamic banks. This study aims to analyze the influence of perceptions, behaviors, and preferences of the merchant community in Pasar Parung on interest in becoming Islamic bank customers. The study used quantitative data analysis methods. The research used a validity test, reliability test, and multiple linear regression analysis. The results showed that the perception of the merchant community influenced the interest in becoming Islamic bank customers. In contrast, the behavior of the merchant community did not affect the interest in becoming Islamic bank customers. The preferences of the merchant community affect the interest in becoming customers of Islamic banks. Simultaneously, perceptions, behaviors, and preferences affect the interest in becoming a customer of Islamic banks. Based on research shows that the public still needs Islamic banking education. Islamic banks are also expected to improve their quality performance to support the success of their operations to attract public interest to become customers of Islamic banks. Keywords: Perception, Behavior, Preferences, Interests, Islamic Bank